(untitled) (World Journal of Vocational Education and Training, 2020)
The study determined the effects of videotaped instructional method on students’ academic achievement in basic technology in secondary schools in the State. Two research questions guided the study while two hypotheses were tested at 0.05 level of significance. The study adopted a non-randomized quasi experimental research design. The population was 11,129 students offering basic technology out which 102 constituted the sample size. Purposive sampling technique was used to select two intact classes. The instrument for data collection was Basic Technology Achievement Test (BTAT) which contained 10 objective questions. The instrument was validated by three experts, and yielded the reliability coefficient 0.84 which was established using Cronbach Alpha. Mean was used to analyze data relating to research questions while Analysis of Covariance (ANCOVA) was used to test the null hypotheses. Findings revealed among others that students taught Basic Technology using videotaped instructional method performed better with higher post-test scores than those taught with conventional method. Sequel to the findings, the researchers concluded that videotaped instructional method could improve students’ academic achievement in Basic Technology. It was therefore recommended among others that basic technology teachers should use videotaped instructional method to enable students effectively learn and assimilate what they leant in order to improve on their academic achievements.